2022
DOI: 10.1108/jqme-02-2021-0018
|View full text |Cite
|
Sign up to set email alerts
|

Reliability centered maintenance (RCM): literature review of current industry state of practice

Abstract: PurposeReliability centered maintenance (RCM) is a process used to determine activities to be taken to ensure an asset continues to perform asset's function in asset's present operating context by identifying asset's function, failure modes that could preclude performing asset's intended function, prioritizing failure modes and determining effective preventative maintenance tasks that can be cost effectively and efficiently implemented to reduce the likelihood of a failure.Design/methodology/approachA comprehe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…To create proactive maintenance plans that increase equipment performance and dependability, RCM concentrates on comprehending failure modes and their effects. RCM has also been extensively applied in industry to lower maintenance costs ( Geisbush & Ariaratnam, 2023 ). According to the preliminary studies by Filz et al (2021) , a popular technique for identifying fault conditions in parts, components, or larger capital goods in advance is FMEA.…”
Section: Resultsmentioning
confidence: 99%
“…To create proactive maintenance plans that increase equipment performance and dependability, RCM concentrates on comprehending failure modes and their effects. RCM has also been extensively applied in industry to lower maintenance costs ( Geisbush & Ariaratnam, 2023 ). According to the preliminary studies by Filz et al (2021) , a popular technique for identifying fault conditions in parts, components, or larger capital goods in advance is FMEA.…”
Section: Resultsmentioning
confidence: 99%
“…Since the introduction of RCMs, many research works, success stories, and applications in various case studies have been reported. Geisbush and Ariaratnam (2023) provided a comprehensive literature review examining 16 industries that have adopted RCM practice. Richet et al (1995) are among the earliest work on applying RCM to improve maintenance strategies in various industrial sectors.…”
Section: Rcm Applicationsan Overviewmentioning
confidence: 99%
“…Since the introduction of RCMs, many research works, success stories, and applications in various case studies have been reported. Geisbush and Ariaratnam (2023) provided a comprehensive literature review examining 16 industries that have adopted RCM practice.…”
Section: Rcm Applications – An Overviewmentioning
confidence: 99%
“…However, regular maintenance also has obvious disadvantages: on the one hand, effective maintenance resources can not be reasonably used, on the other hand, it may excessively increase the maintenance burden of equipment, resulting in the reduction of working life. Especially with the increasing requirement of continuous gas transmission for the long-cycle stability of the compressor system, it is increasingly difficult to meet the current needs of gas transmission work and maintenance management [3] . Through the continuous summary of the research results, the reliability-centered maintenance (RCM) is based on the equipment failure mode and failure consequence system analysis, reasonably uses logical inference to complete the formulation of maintenance strategy, and improves the reliability of the compressor in the most economical method.…”
Section: Introductionmentioning
confidence: 99%